Sugiatno, Muhammad Rif’at, Agung Hartoyo, Dede Suratman, Achmad Yani, Hamdani - Sugiatno Sugiatno; Muhammad Rif’at; Agung Hartoyo; Dede Suratman; Achmad Yani; Hamdani Hamdani; Bistari Bistari (JPKM (Jurnal Pengabdian Kepada Masyarakat) UNTAN, 2021)
Regardless of the situation, even though there are no signs that the Covid 19 pandemic will end - education must continue to run in accordance with the mandate of the law on the applicable curriculum. As understood by various parties related to mathematics learning in schools, teachers must balance spiritual and social attitudes, knowledge and skills, and apply them in various situations in schools and communities. This mandate implied that the core competence of spiritual attitude KI-1 and KI-2 became the main pillar for KI-3 and KI-4 in all subjects. One of the reasons why these two core competencies were only the tasks of Religion and PPKn subjects, namely spiritual competence and too forced attitudes that interfered with scientific substance and cause confusion and excessive administrative burden for teachers (Kemendikbud, 2017). Assessment of the attitudes of KI-1 and KI-2 had been eliminated in every subject, except for religion and PPKn. However, IP was still included in the writing of the Lesson  Plan (RPP). With a background like this, it implied a problem that deserved to be handled through this PKM activity. The main problem was how to formulate KI-1 and KI-2 into lesson plans and how to measure them in SMP mathematics learning. Through workshops with action research, an implementative lesson plan was produced that fulfills the theoretical principles of planning mathematics learning.